Citizen soldiers in the War of 1812 - Skeen, Carl Edward
Winner of the Army Historical Foundation Book AwardDuring the War of 1812, state militias were intended to be the primary fighting force. Unfortunately, while militiamen showed willingness to fight, they were untrained, undisciplined, and ill-equipped. These raw volunteers had no muskets, and many did not know how to use the weapons once they had been issued. Though established by the Constitution, state militias found themselves wholly unprepared for war. The federal government was empowered to use these militias to ""execute the laws of the Union, suppress insurrections, and repel invasions.